Bridging the Tactile Gap: Evaluating Virtual Reality (VR) Laboratories in Distance Life-Science Curricula - Ruth Rize Paas Megahati S; H. L. M. Mohideen (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
The persistent expanding trajectory of distance education within higher biological sciences has encountered structural friction regarding the "tactile gap"—the systemic inability of remote students to acquire manual laboratory competencies, sensory-spatial familiarization, and procedural confidence through flat, two-dimensional digital interfaces. This literature review evaluates the implementation of Virtual Reality (VR) laboratories as an immersive instructional solution within distance life-science curricula. The objective is to synthesize evidence regarding VR's impact on conceptual retention, cognitive load, and spatial-procedural skill acquisition, while critically analyzing infrastructural barriers and pedagogical integration frameworks. Employing a comprehensive review framework encompassing 50 major studies from 2020 to 2026, the findings demonstrate that high-fidelity, fully immersive VR environments achieve a statistically significant equivalent or superior conceptual gain compared to conventional brick-and-mortar laboratories. Crucially, VR effectively mitigates intrinsic cognitive load by chunking complex macromolecular structures, though it introduces risks of extraneous load via cyber-sickness. The review identifies a critical transition from isolated VR software towards hybrid, AI-augmented, and cloud-rendered ecosystems. We propose a "Tactile-Immersive Scaffolding Framework" to guide distance educators in balancing experiential realism with digital accessibility, establishing that VR does not dilute academic rigor but structurally expands the democratization of experiential scientific education.